A Feasibility study on Natural Ylang-Ylang oil - Claudio, Kristine R.; De Guzman, Elaine F.; Ruiz, Dida Rowena S. (Diliman, Quezon City College of Engineering, 1998)
L'essentiale Natural Ylang-Ylang Oil has a powerfully sweet, exotic fragrance. It acts as a minor constituent in the manufacture of cosmetic products. The company would like to capture 53.671% of the excess demand on the first year, 8.804% in the second year, 16.887% in the thrid year, 19.739% in the fourth year until it reaches a market share of 23.297% on the fifth year. In order to capture its target market share, a marketing strategy for the product was developed. The product shall be packaged under the company name L'essentiale, which means 'the essential'. A green globe in the shape of a drop of oil will serve as the company logo. L'essentiale Ylang-Ylang Oil will be sold at P7,100 per liter which is 6.25% cheaper than the imported essential oils. product sampling, brochure distribution, and symposium sponsorship shall be done to introduce the product to the market. the marketing budget is P746,240,000. L'essentiale Ylang-Ylang Oil will be produced through hydrostream distillation in a plant that will be built in a 1,507 square meter land located at number 838-F San Roque Anao, Tarlac. The company will be hiring 23 production workers to meet its desired output. the total project cost is estimated to be around P36,197,927.51. Individuals investing in the form of company stocks will finance the corporation. Common stocks for the company shall be issued to raise an owner's equity of 70% of the total project cost while the remaining 30% will be loaned from SSS-Kasapi. The owner's equity is P25,338,549.26. Therefore, an amount of P10,859,378.25 will be loaned. The project is financially feasible with a payback of 3 years and 4 months , anet present value of P9,704,437.64 and an internal rate of retuen 27.67% given the minimum attractive rate of return is 20%. the production of ylang-ylang oil will be under the ownership of L'essentiale Corporation with a total of 46 employees, 23 employees in the administrative division and 23 production workers. The establishment of L'essentiale Ylang-Ylang Oil is socio-economically profitable. It offers natural ylang-ylang oil to manufacturers of cosmetic products at a price 6.25% cheaper than imported essential oils. It also provides additional government revenues by paying P5,234,381.83 municipal tax and P86,298,011.97 corporate tax. It also provides additional income to the Department of Science and Technology and the residents of Anao, Tarlac by making them suppliers of equipment and raw materials, respectively.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: L'essentiale.; Essences and essential oils; Aromatherapy; Participatory monitoring and evaluation (Project management)